Design for tomorrow: future-proof arctic architecture in cognizance of shifts in climate and regional livelihood - Wetteskind, Sarah (Laurentian University of Sudbury, 2022)
Accelerating climate change is dramatically altering environments worldwide, which also has significant impacts on cultural practices and livelihoods in vulnerable regions. Warming at three times the global average, the Arctic and its Inuit population are in a precarious state. This Thesis thus focuses on the future-proofing of the Torngat Mountains National Park Base Camp and Research Station (Nunatsiavut, Labrador). Informed by predictive climate models and a review of architectural strategies to respond to inevitable and expected climate change, the Base Camp is redesigned to ensure short-term and long-term adaptability and resilience. The design is simultaneously informed by land-based ecological and cultural lessons, connecting the building back to the people and supporting the traditional livelihood that is intrinsically linked to their land. The meeting of researchers, Inuit, and tourists in this place should foster opportunities to learn from one another about mitigating and adapting to changes to preserve land and livelihood. Master of Architecture (M.Arch)